Development of Prototype System Design with the Application of Renewable Technology - Diah Widiastuti; Titi Ratnasari; Intan Ratna Sari Yanti (Politeknik Pertanian Negeri Samarinda, 2023)
The development of a system designed in such a way as to become a security that makes everyone feel the need to ensure the security of everything that includes himself, both from his activities, and the assets he owns. The magnitude of the value of an asset owned, which encourages everyone to implement an effective and efficient security system as protection. One of them is in Locker cabinets which generally still use a manual locking system. The purpose of this research is to design a locker cabinet door security system by utilizing the Arduino Uno R3-based keypad and E-KTP. This system uses an RFID Reader with a frequency of 13.56 MHz and an ATMega328 Microcontroller which acts as a controller or circuit controller and is tested with hardware and software testing to determine the performance between software and hardware on the device. The result of this research is that the RFID Reader can detect E-KTP with a maximum distance of 2.5 cm and the solenoid will lock back after 3 seconds. Utilization of Renewable Energy is currently a priority in carrying out technology development, one of which is the use of solar energy with solar panels as electrical energy. This research is to support efforts to develop energy-based technology that is converted with various supporting components and system authentication designed using the use of control security systems both in terms of administration and information technology based on population data and uncontrolled system prototypes.